2006
DOI: 10.1074/jbc.m606543200
|View full text |Cite
|
Sign up to set email alerts
|

Human Erythrocyte Membranes Contain a Cytochrome b561 That May Be Involved in Extracellular Ascorbate Recycling

Abstract: Human erythrocytes contain an unidentified plasma membrane redox system that can reduce extracellular monodehydroascorbate by using intracellular ascorbate (Asc) as an electron donor. Here we show that human erythrocyte membranes contain a cytochrome b 561 (Cyt b 561 ) and hypothesize that it may be responsible for this activity. Of three evolutionarily closely related Cyts b 561 , immunoblots of human erythrocyte membranes showed only the duodenal cytochrome b 561 (DCytb) isoform. DCytb was also found in guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 59 publications
(77 reference statements)
4
76
0
Order By: Relevance
“…2 and 4). In further support of a causal connection between ascorbate efflux, ferrireduction, and 55 Fe-labeled iron uptake it was observed that, as with the former two, the addition of 50 M cytochalasin B to the cells largely removed the dose response to exogenous DHA addition (Fig. 5B).…”
Section: K562 Cells Import Dha and Reduce It Intracellularly Tosupporting
confidence: 53%
See 2 more Smart Citations
“…2 and 4). In further support of a causal connection between ascorbate efflux, ferrireduction, and 55 Fe-labeled iron uptake it was observed that, as with the former two, the addition of 50 M cytochalasin B to the cells largely removed the dose response to exogenous DHA addition (Fig. 5B).…”
Section: K562 Cells Import Dha and Reduce It Intracellularly Tosupporting
confidence: 53%
“…Non-transferrin 55 Fe-labeled Iron Uptake from Ferric Citrate Is Regulated by DHA Uptake and Ascorbate Efflux-K562 cells grown replete with iron in the presence of 10% fetal bovine serum (see "Experimental Procedures") had a mean basal iron content of 390 Ϯ 41 pmol of iron per million cells. On the basis of our observations that K562 cells can recycle ascorbate across the plasma membrane and subsequently reduce extracellular NTBI as a result, experiments were conducted to assess the capacity of this redox cycling to affect NTBI uptake from radiolabeled [ 55 Fe]ferric citrate.…”
Section: K562 Cells Import Dha and Reduce It Intracellularly Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The Glycine max orthologue of AIR12 and CIL1 was identified as a cytochrome b561 isoform that binds a single heme in vitro and was postulated to interact with members of the plasma membrane redox system (Preger et al 2009). In mammals, cytochrome b561 is involved with ascorbate regeneration across membranes (Su et al 2006). In plants, ascorbate plays a role in scavenging ROS generated through photosynthesis pathways (Bowler et al 1991;Smith and Veitch 1998;Scandalios 2005).…”
Section: Involvement Of Ros During Auxin and Aba-induced Lateral Growthmentioning
confidence: 99%
“…Ascorbic acid protects lipids by scavenging aqueous oxidants and by reducing tocopheroxyl radicals in the lipid bilayer (45,46). Intact RBCs reduce extracellular ferricyanide to ferrocyanide via the activity of a trans-plasma membrane oxidoreductase that uses ascorbic acid as an electron donor (47,48). As a consequence treatment with ferricyanide depletes the ascorbate/tocopherol antioxidant defence system.…”
Section: Exogenous Oxidative Insult Increases Bodipy 581/ 591-pc Oxidmentioning
confidence: 99%